A Comparative Chronology for Western Iran, 1500-500 B.C. - Young, Jr. T. Cuyler
New Material from Hasanlu and Ziweye. The Internal Chronology and Cultural Relationships of Hasanlu VI to III. Ziweye – The Stratigraphy and Internal Chronology of Tepe Sialk, Tepe Giyan and the Achaemenid Village at Susa. Comparative Typology and Chronology. Typological Comparisons. The Early Western Grey Ware Horizon. The Late Buff Ware Horizon. The Late Western Grey Ware Group. Relative Chronology. Absolute Dates. The Late Buff Ware Horizon. The Early Western Grey Ware Horizon. Conclusion.